Fluorene exposure among PAH-exposed workers is associated with epigenetic markers related to lung cancer - Alhamdow, Ayman (Occup Environ Med, 2020)
OBJECTIVES: Exposure to high-molecular-weight polycyclic aromatic hydrocarbons (PAHs) may cause cancer in chimney sweeps and creosote-exposed workers, however, knowledge about exposure to low-molecular-weight PAHs in relation to cancer risk is limited. In this study, we aimed to investigate occupational exposure to the low-molecular-weight PAHs phenanthrene and fluorene in relation to different cancer biomarkers. METHODS: We recruited 151 chimney sweeps, 19 creosote-exposed workers and 152 unexposed workers (controls), all men. We measured monohydroxylated metabolites of phenanthrene and fluorene in urine using liquid chromatography coupled to tandem mass spectrometry. We measured, in peripheral blood, the cancer biomarkers telomere length and mitochondrial DNA copy number using quantitative PCR; and DNA methylation of F2RL3 and AHRR using pyrosequencing. RESULTS: Median PAH metabolite concentrations were higher among chimney sweeps (up to 3 times) and creosote-exposed workers (up to 353 times), compared with controls (p<0.001; adjusted for age and smoking). ∑OH-fluorene (sum of 2-hydroxyfluorene and 3-hydroxyfluorene) showed inverse associations with percentage DNA methylation of F2RL3 and AHRR in chimney sweeps (B (95% CI)=–2.7 (–3.9 to –1.5) for F2RL3_cg03636183, and –7.1 (–9.6 to –4.7) for AHRR_cg05575921: adjusted for age and smoking), but not in creosote-exposed workers. In addition, ∑OH-fluorene showed a 42% mediation effect on the inverse association between being a chimney sweep and DNA methylation of AHRR CpG2. CONCLUSIONS: Chimney sweeps and creosote-exposed workers were occupationally exposed to low-molecular-weight PAHs. Increasing fluorene exposure, among chimney sweeps, was associated with lower DNA methylation of F2RL3 and AHRR, markers for increased lung cancer risk. These findings warrant further investigation of fluorene exposure and toxicity.